'Don't play the butter notes': jazz in medical education. Issue 1 (1st January 2016) - Bradner, Melissa; Harper, Darryl V.; Ryan, Mark H.; Vanderbilt, Allison A.
Abstract : Jazz has influenced world music and culture globally – attesting to its universal truths of surviving, enduring, and triumphing over tragedy. This begs the question, what can we glean in medical education from this philosophy of jazz mentoring? Despite our training to understand disease and illness in branching logic diagrams, the human experience of illness is still best understood when told as a story. Stories like music have tempos, pauses, and silences. Often they are not linear but wrap around the past, future, and back to the present, frustrating the novice and the experienced clinician in documenting the history of present illness. The first mentoring lesson Hancock discusses is from a time he felt stuck with his playing – his sound was routine. Miles Davis told him in a low husky murmur, 'Don't play the butter notes'. In medical education, 'don't play the butter notes' suggests not undervaluing the metacognition and reflective aspects of medical training that need to be fostered during the early years of clinical teaching years.